1996
DOI: 10.1542/pir.17-5-175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Function During Childhood

Abstract: There are several methods to evaluate renal function during childhood. The use of serum creatinine, either alone or in combination with the Schwartz formula, is reliable and quick, but requires knowledge of conceptual age. A plasma creatinine concentration of 88.4 mumol/L (1.0 mg/dL), for example, represents normal renal function in an adolescent but more than 50% loss of renal function in a 5-year-old child. A timed urine collection for creatinine clearance is another evaluative method, but the adequacy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 0 publications
0
32
0
3
Order By: Relevance
“…In the clinical setting, GFR is most frequently estimated by creatinine clearance, which correlates with serum creatinine levels. Serum creatinine increases during childhood as a consequence of increased muscular mass, whereas creatinine clearance (ml/min per 1.73 m 2 ), increases rapidly during the first year of life and stabilizes thereafter (22).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, GFR is most frequently estimated by creatinine clearance, which correlates with serum creatinine levels. Serum creatinine increases during childhood as a consequence of increased muscular mass, whereas creatinine clearance (ml/min per 1.73 m 2 ), increases rapidly during the first year of life and stabilizes thereafter (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has, therefore, been suggested that the diagnosis of renal dysfunction in preterm infants should be based on reference charts rather than on a single cutoff value during the early neonatal period. 2,3 While reference data are available for both term and moderately preterm infants, [4][5][6][7][8] there are limited data in extremely premature babies born at <28 weeks gestation, especially in the first few days of life. Available data suggest that creatinine levels in these babies are much higher than in more mature preterm babies during the first few days of life, decreasing thereafter to the normal term reference range.…”
Section: Introductionmentioning
confidence: 99%
“…Serum Cr level is still widely used in current clinical studies to define neonatal AKI 6,7) despite its limitations of being influenced by maternal-fetal transplacental transfer, body mass, and maturation variability [8][9][10][11] . Furthermore, elevation of serum Cr level is a reflec tion of decreased renal function, not a marker of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serum Cr levels can vary depending on age, gender, muscle mass, medication, and intravascular volume status 8) . Furthermore, elevation of serum Cr level is not a marker but a consequence of kidney injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation